2018
DOI: 10.3989/gya.1217172
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and seasonal changes in the fatty acid profile of Uruguayan “Colonia” Cheeses

Abstract: SUMMARY:The basic chemical composition and the fatty acid (FA) profile of Uruguayan Colonia cheese, consumed in the Mercosur region, were determined. 24 cheeses from different dairy farms: 10 elaborated in autumn and 14 in spring, were analyzed. Those cheeses are made from cow´s milk, whose diet was composed of 50% pasture system, 25% concentrate, and 25% silage reserves. The cheese making and ripening time were similar. Seasonal differences emerged in the profiles of saturated FA (SFA), unsaturated FA (UFA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…In the raw, pasteurised and UHT bovine milk analysed by Pestana et al (2015), the n-6/n-3 ratio was 3.51, 3.47 and 3.49, respectively. The n-6/n-3 ratio in the 'Colonia' cheeses produced from cow milk in the autumn was 3.29 and 4.47 in the cheeses produced in the spring (Hirigoyen et al 2018). According to data in the literature (Wijendran & Hayes 2004;Simopoulos 2008), an adequate intake of both n-6 and n-3 fatty acids is essential for good health and for lowering the risk of cardiovascular disease and type 2 diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…In the raw, pasteurised and UHT bovine milk analysed by Pestana et al (2015), the n-6/n-3 ratio was 3.51, 3.47 and 3.49, respectively. The n-6/n-3 ratio in the 'Colonia' cheeses produced from cow milk in the autumn was 3.29 and 4.47 in the cheeses produced in the spring (Hirigoyen et al 2018). According to data in the literature (Wijendran & Hayes 2004;Simopoulos 2008), an adequate intake of both n-6 and n-3 fatty acids is essential for good health and for lowering the risk of cardiovascular disease and type 2 diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…In fresh goat cheeses analyzed by Cossignani et al [50], the n-6/n-3 ratio was 7.0, and in goat semi-hard cheeses, it was 3.3. According to Hirigoyen et al [51], the n-6/n-3 ratio was 3.29 in "Colonia" cheeses produced from cow milk in autumn and 4.47 in those produced in the spring. In sheep and goat cheeses analyzed by Milewski et al [44], the n-6/n-3 ratio was lower (reading 3.42 and 2.94, respectively) compared to the sheep and goat cheeses analyzed in the presented study.…”
Section: Fatty Acid Composition and Lipid Quality Indices In Cheesesmentioning
confidence: 99%
“…Cossignani et al [50] reported that the AI value was 2.9 in goat milk, 2.7 in fresh cheese samples, and 2.4 in semi-hard cheese samples. Hirigoyen et al [51] reported that AI and TI values calculated for "Colonia" cheese produced from cow milk in the autumn and in the spring were 2.21 and 2,84, respectively for both seasons. According to Ulbricht and Southgate [6], the AI and TI indices might better characterize the atherogenic and thrombogenic potential of the diet than the PUFA/SFA ratio.…”
Section: Fatty Acid Composition and Lipid Quality Indices In Cheesesmentioning
confidence: 99%
“…The discrimination performance of the fatty acids profiles for classifying the Serra da Estrela cheese samples taking into account the cheese production dates (November 2017 to March 2018, independently of the cheese producer or the geographical origin) was further investigated. Seasonal changes of the fatty acids profile are expected and were reported, for example, by Hirigoyen et al [2] for Uruguayan "Colonia" cheeses, produced with cow milk during autumn and spring. Using the proposed chemometric approach, a LDA-SA model with four significant discriminant functions (explaining the first three functions 98% of the data variability) was developed.…”
Section: Fatty Acids Profile As a Biomarker Fingerprint For Assessingmentioning
confidence: 55%
“…Consumers perceive cheese as a food product rich in nutritionally controversial saturated fatty acids (SFA), which are associated to high cholesterol and cardiovascular diseases although recent studies show different tendencies. However, cheese is also a source of some health-promoting mono-and polyunsaturated fatty acids (MUFA and PUFA, respectively) as well as short chain fatty acids (SCFA) and certain trans-fatty acids that are considered as part of a healthy diet [1,2].…”
Section: Introductionmentioning
confidence: 99%